Assessing grammar - Purpura, James E. (Cambridge, U.K : New York : Cambridge University Press, 2005)
This title examines current language assessment instruments, outlines in an accessible manner the research in the field, and provides language teachers and test developers with practical guidelines to enable them to develop suitable assessment tools for their students.
Includes bibliographical references (p. 275-290) and index.
Keywords: Second language acquisition; Grammar, Comparative and general; Language and languages -- Grammars